Does cold shock treatment extend the shelf life of avocado fruit? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Food Technology at Massey University, Palmerston North, New Zealand - Vo, Dong Hoai (Massey University, 2020)
Avocado ripens rapidly after harvest causing the difficulty for fruit export to distant markets. Cold storage at 4 – 6 °C is the most popular method to extend the shelf-life of avocado for 4 weeks. Chen et al. (2017) showed that cold shock treatment (CST) at 0 °C for 30 mins effectively delayed ripening-associated processes, reduced respiration rate, ethylene production and cell-wall enzyme activities. The objective of this thesis was to provide better insight into the effects of CST on delaying avocado ripening by observing the influence of CST on post-storage qualities of avocado. The experiments replicated the experimental work of Chen et al. (2017). Experiment 1 was to identify the suitable CST in a full matrix of three temperatures (0, 2 and 4 °C) and six durations (15, 30, 45, 60, 90 and 120 minutes). The effects of CST were not observed on firmness retention measured by puncture test, however, there was a consistent trend that colder temperatures and shorter treatments resulted in better firmness outcomes although there are not statistically significant, possibly due to the large fruit variability. Experiment 2 was to replicate the experiment 1 with increased sample size to 3 times to reduce the influence of fruit to fruit variation on the data analysis. The effects of CST on firmness retention were not seen. The large fruit variability still remained the big issue. Experiment 3 was designed to increase the sample size to 10 times compared to the previous experiment to minimise the large fruit variability using a selected single treatment (0 °C and 60 minutes). The effect of CST treatment on the ripening (including pulp softening, skin discolouration, respiration rate and ethylene production rate) was not statistically significant, however, the considerable reduction of ethylene production rate was observed. Experiment 4 was designed to provide better insight about the effects of CST on the overall qualities of avocado using 2 different methods for firmness measurements (destructive and non-destructive method). The effects of CST on the ripening was insignificant, however, ethylene production rate significantly reduced with treated fruit. Nevertheless, unlike the experiment results of Chen et al. (2017), in the current study, CST was not found to have any pronounced effects on fruit quality through 4 experiments.
Figures are re-used with permission.
Keywords: 300806 Post harvest horticultural technologies (incl. transportation and storage); 300604 Food packaging, preservation and processing